Where did dinosaurs come from? - Zoehfeld, Kathleen Weidner (Let's-read-and-find-out science., 2010)
Presents information about the evolution of the dinosaurs, from the earliest four-limbed tetrapos of the Paleozoic age, to the meat-eating eoraptors of early Triassic, to the fully-developed dinosaurs of the Jurassic and Cretaceous periods.